Evolving computed tomography angiography for aortic valve replacement: Optimizing transcatheter and surgical therapies. Issue 12 (28th September 2022) - Tully, Andrew; Tom, Stephanie; Xie, Joe; O'Brian, Colin; Gleason, Patrick; Grubb, Kendra J.
Abstract: Transcatheter aortic valve replacement (TAVR) has transformed the treatment of aortic stenosis and pre‐procedure planning relies heavily on advanced imaging. Multidetector computed tomography angiography, the "TAVR CT, " facilitates essential planning steps of measuring the aortic root for valve sizing and feasibility and assessment of potential access vessels, making it the guideline gold standard in preprocedural TAVR work up. This Impact of Advanced Imaging Techniques on Cardiac Surgery article will examine the development of TAVR CT, illustrate the current impact and utility, and highlight potential areas of future growth. Clinicians who keep informed of these changes and can become proficient with TAVR CT analyses will offer patients the most optimal results and fuel future therapeutic growth.